Short-term effects of transcranial direct current stimulation on motor speech in Parkinson's disease: a pilot study - Brabenec, Lubos; Kovac, Daniel; Mekyska, Jiri; Rehulkova, Lenka; Kabrtova, Veronika; Rektorova, Irena (Journal of neural transmission (Vienna, Austria, 2024)
INTRODUCTION: Hypokinetic dysarthria (HD) is a common motor speech symptom of Parkinson's disease (PD) which does not respond well to PD treatments. We investigated short-term effects of transcranial direct current stimulation (tDCS) on HD in PD using acoustic analysis of speech. Based on our previous studies we focused on stimulation of the right superior temporal gyrus (STG) - an auditory feedback area. METHODS: In 14 PD patients with HD, we applied anodal, cathodal and sham tDCS to the right STG using a cross-over design. A protocol consisting of speech tasks was performed prior to and immediately after each stimulation session. Linear mixed models were used for the evaluation of the effects of each stimulation condition on the relative change of acoustic parameters. We also performed a simulation of the mean electric field induced by tDCS. RESULTS: Linear mixed model showed a statistically significant effect of the stimulation condition on the relative change of median duration of silences longer than 50 ms (p = 0.015). The relative change after the anodal stimulation (mean = -5.9) was significantly lower as compared to the relative change after the sham stimulation (mean = 12.8), p = 0.014. We also found a correlation between the mean electric field magnitude in the right STG and improvement of articulation precision after anodal tDCS (R = 0.637; p = 0.019). CONCLUSIONS: The exploratory study showed that anodal tDCS applied over the auditory feedback area may lead to shorter pauses in a speech of PD patients.
Keywords: řeč; výsledek terapie; Male; Speech; Temporal Lobe; klinické křížové studie; Hypokinetic dysarthria; pilotní projekty; spánkový lalok; Transcranial Direct Current Stimulation; Parkinson’s disease; přímá transkraniální stimulace mozku; Aged; mužské pohlaví; senioři; Superior temporal gyrus; Treatment Outcome; Transcranial electric stimulation; lidé; ženské pohlaví; Humans; Cross-Over Studies; Dysarthria; Pilot Projects; Female; dysartrie; Parkinsonova nemoc; Parkinson Disease; lidé středního věku; Acoustic analysis; Middle Aged